Co-occurrence of Beckwith-Wiedemann syndrome and pseudohypoparathyroidism type 1B: coincidence or common molecular mechanism? - Pignata, Laura; Cecere, Francesco; Acquaviva, Fabio; D’Angelo, Emilia; Cioffi, Daniela; Pellino, Valeria; Palumbo, Orazio; Palumbo, Pietro; Carella, Massimo; Sparago, Angela; De Brasi, Daniele; Cerrato, Flavia; et al. (Frontiers in Cell and Developmental Biology, 2023)
Imprinting disorders are congenital diseases caused by dysregulation of genomic imprinting, affecting growth, neurocognitive development, metabolism and cancer predisposition. Overlapping clinical features are often observed among this group of diseases. In rare cases, two fully expressed imprinting disorders may coexist in the same patient. A dozen cases of this type have been reported so far. Most of them are represented by individuals affected by Beckwith–Wiedemann spectrum (BWSp) and Transient Neonatal Diabetes Mellitus (TNDM) or BWSp and Pseudo-hypoparathyroidism type 1B (PHP1B). All these patients displayed Multilocus imprinting disturbances (MLID). Here, we report the first case of co-occurrence of BWS and PHP1B in the same individual in absence of MLID. Genome-wide methylation and SNP-array analyses demonstrated loss of methylation of the KCNQ1OT1:TSS-DMR on chromosome 11p15.5 as molecular cause of BWSp, and upd(20)pat as cause of PHP1B. The absence of MLID and the heterodisomy of chromosome 20 suggests that BWSp and PHP1B arose through distinct and independent mechanism in our patient. However, we cannot exclude that the rare combination of the epigenetic defect on chromosome 11 and the UPD on chromosome 20 may originate from a common so far undetermined predisposing molecular lesion. A better comprehension of the molecular mechanisms underlying the co-occurrence of two imprinting disorders will improve genetic counselling and estimate of familial recurrence risk of these rare cases. Furthermore, our study also supports the importance of multilocus molecular testing for revealing MLID as well as complex cases of imprinting disorders.